2000
DOI: 10.1016/s0014-5793(99)01749-4
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding structure–function relationships in respiratory chain complex II

Abstract: Complex II (succinate:quinone oxidoreductase) of aerobic respiratory chains oxidizes succinate to fumarate and passes the electrons directly into the quinone pool. It serves as the only direct link between activity in the citric acid cycle and electron transport in the membrane. Finer details of these reactions and interactions are but poorly understood. However, complex II has extremely similar structural and catalytic properties to quinol :fumarate oxidoreductases of anaerobic organisms, for which X-ray stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
85
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 49 publications
5
85
0
2
Order By: Relevance
“…The anchor domain was proposed to contain a core of four antiparallel helices comprising helices I, II, IV, and V (4, 26). This model is now supported by two crystal structures (10,27,28).Several lines of experimentation have shown that the membrane domain contains the binding sites for quinone substrates. First, functional anchor polypeptides are required for interaction with quinone substrates (1, 3).…”
mentioning
confidence: 74%
“…The anchor domain was proposed to contain a core of four antiparallel helices comprising helices I, II, IV, and V (4, 26). This model is now supported by two crystal structures (10,27,28).Several lines of experimentation have shown that the membrane domain contains the binding sites for quinone substrates. First, functional anchor polypeptides are required for interaction with quinone substrates (1, 3).…”
mentioning
confidence: 74%
“…12 We report here the cellular events deriving from Complex II mutation associated with Leigh's syndrome. This study was conducted also in cellular models in which we mimicked Complex II deficiency by using Complex II inhibitors.…”
mentioning
confidence: 99%
“…These autosomerecessive conditions manifest as childhood encephalopathy, myopathy, adult optic atrophy, and Leigh syndrome. However, mutations in subunit SdhB, SdhC, or SdhD are linked to tumorigenesis in the form of autosome-dominant familial paragangliomas and pheochromocytomas (1,3,16,19,33). Paragangliomas are benign, highly vascular tumors located within sympathetic paraganglia in the head and neck, and they are derived from neural crest cells (38).…”
mentioning
confidence: 99%
“…Complex II oxidizes succinate to fumarate and transfers the electrons to ubiquinone through a sequence of steps involving a flavin moiety in SdhA, a set of iron-sulfur clusters in SdhB, a heme group in SdhC, and the ubiquinone binding site in SdhC and SdhD ( Fig. 1) (1,9). When complex II is disrupted at SdhB, SdhC, or SdhD, the succinate dehydrogenase activity within SdhA can remain intact even though overall complex II function is disabled (51).…”
mentioning
confidence: 99%